Cervical Necrotizing Fasciitis of Odontogenic Origin in a Diabetic Patient Complicated by Substance Abuse - Camino Junior,Rubens (2014)
Cervical necrotizing fasciitis (CNF) is an uncommon, potentially fatal soft tissue infection with rapid progression characterized by necrosis in the subcutaneous tissue and fascia. A case of CNF of odontogenic origin in a diabetic patient, complicated by alcohol dependence and tobacco abuse, is presented with a literature review. The emergency procedure comprised hydration, colloid administration, glycemic control and broad spectrum antibiotic therapy, followed by aggressive surgical debridement. Necrosis in the platysma muscle was verified by histopathologic analysis. Reconstructive surgery was performed after suppressing the infection, and the wound was closed with an autologous skin graft. The patient had a long hospital stay, in part because the substance abuse led to a difficult recovery. The principles of early diagnosis, aggressive surgical debridement, broad-spectrum antibiotic therapy and intensive supportive care in the treatment of CNF were confirmed in the present case. It was concluded that given the occurrence of CNF in the presence of diabetes mellitus and abuse of substances such as alcohol and tobacco, the health care professional should consider a stronger response to treatment and longer hospitalization.